Analysis Of Service Quality On Customer Satisfaction With Servqual And QFD Methods: Analisis Kualitas Pelayanan Terhadap Kepuasan Pelanggan Dengan Metode Servqual Dan QFD - Wahyu Satria Perkasa (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2022)
This study aims to analyze the problem and produce alternative proposals in increasing customer satisfaction at PT. Mentari Trans Nusantara in Sidoarjo. The analytical tool used is tabulating the questionnaire, collecting data in the form of validity testing and reliability testing. The hypothesis in this study is that there is an Analysis of Service Quality on Customer Satisfaction. The method used is the Servqual and QFD methods. The Servqual method is used to determine the extent to which the gap between customer perceptions and expectations ha an impact on the realization of customer satisfaction. QFD method is used to clarify to make improvements. The results of this study indicate that the service variable attributes that do not meet customer satisfaction are the dimensions of reliability and the value of the level of satisfaction, namely: employees provide maximum service to customers, employees are able to resolve complaints faced by customers, package delivery which is always done quickly and on time, employees have the knowledge to answer customer questions, and the timeliness of service is in accordance with the promises given.